A case report of adult rectal duplication cyst resected by synchronous trans-abdominal and trans-anal total mesorectal excision. (2020) - Tominaga, Tetsuro; Nonaka, Takashi; Fukuda, Akiko; Moriyama, Masaaki; Oyama, Syouzaburou; Hidaka, Shigekazu; Tabata, Kazuhiro; Sawai, Terumitsu; Nagayasu, Takeshi
Highlights: Rectal duplication cyst is extremely rare. Adult onset rectal duplication cyst usually contains malignant formation. Complete tumor resection is needed for the disease to prevent malignant change. Synchronous trans abdominal and anal approach was effective for complete tumor resection. Abstract: Introduction: Rectal duplication cyst is extremely rare. Most of the cases diagnosed before two years old. Adult onset rectal duplication cyst usually contains malignant formation. Then complete tumor resection is needed for the disease to prevent malignant change. Presentation of case: A 52-year-old man was referred to our hospital due to bloody stool. Colonoscopy showed 20-mm of sub-mucosal tumor at low rectum. Biopsy revealed no specific findings. Abdominal computed tomography showed that a 20-mm low density mass at posterior of lower rectum. As the existence of malignant lesion was unassailable, we planned two team, trans abdominal and trans-anal, laparoscopic low anterior resection. Perioperative course was good. Macroscopically, rectum had a submucosal cystic mass fulfilled mucinous content. Histologically, cyst wall was covered with heterotopic ciliated epithelium and composed of smooth muscle. Discussion: Trans-anal total mesorectal excision (ta-TME) was introduced as beneficial approach for rectal malignancies. Conclusion: Complete resection was possible by TME was necessary for patients with adult rectal duplication cyst, and synchronous trans-abdominal and trans-anal approach is a promising option.